Flotation bubble size distribution rules with ultrasonic radiation - Wang Weidong; Zhang Nan (矿业科学学报, 2018)
By a self-made ultrasonic flotation experimental device and image processing method,flotation micro-bubble size distribution and the relationship between rising velocity and size has been investigated under different ultrasonic frequencies (28 kH、60 kHz、120 kHz) and different air velocities (20 mL/min、30 mL/min、40 mL/min) conditions. Results show that ultrasonic irradiation with a certain frequency can change the diameter of flotation bubble,and promote the aggregates of bubbles,60 kHz ultrasonic can promote bubble size significantly,and the average size of bubble aggregates can increase 0.2-0.8 mm. Under ultrasonic field,the second Bjerknes force between bubbles is the major reason for the bubble aggregates,however the aeration velocity has negligible influence on bubble size and bubble coagulation. There is no relationship between the bubbles rising velocity and bubble size,and ultrasonic frequency at the bottom of the floatation unit and the average rising velocity is 15 mm/s. The rising velocity is increasing with the increases of bubbles size at the middle of flotation unit. The average rising velocity reach the peak up to 35 mm/s under 60 kHz ultrasonic field,which is about 17 mm/s higher than that under 28 kHz and 120 kHz ultrasonic field.